Learning scorecard gamification: Application of the MDA framework - Pedroso, T.; Cardoso, E.; Rações, F.; Baptista, A.; Barateiro, J. (Information Systems for Industry 4.0: Proceedings of the 18th Conference of the Portuguese Association for Information Systems, 2019)
The application of gamification techniques in higher education can be challenging. At times it is easy to lose focus and we can no longer explain the connections between players’ motivation and the several elements of the game. This study focused on the application of the MDA framework (Mechanics, Dynamics and Aesthetics) to the platform Learning Scorecard (LS), currently used by several students at ISCTE - Instituto Universitário de Lisboa. The LS is a platform for Learning Analytics that has been used since 2016, on courses of Data Warehouse and Business Intelligence. LS has two views: the student and teacher views. In this work, we will report on the application of the MDA framework to the student view of LS. This view aims to improve the learning experience of students increasing their engagement and motivation through the use of gamification.